The slave as a social being: a critical analysis of modern Brazilian slavery - Alves, Leonardo Dias (Argumentum, 2024)
This article evidences the institutionalisation of modern slavery, and the transformation of social beings into enslaved people, as a starting point for an analysis of the racial division of labour within the Brazilian historical process. Considering enslaved people as a social beings aims to avoid any analysis that restricts the enslaved person to the perspective of a thing. The analysis is based on the ontology of the Marxist social being, founded on the exploitation of an enslaved workforce and the institutionalisation of modern slavery as the mode of production prevalent in Brazil for approximately four hundred years. It demonstrates that in order to approach the genesis of the racial division of labour in Brazilian slavery, a critical understanding of the enslaved as social beings is required.